SISTEM PENGENDALIAN INTERNAL - Juniansen Siregar; Bunga Ria Letisia Sirait; Elpiah Risdayani (At-Tanmiyah Jurnal Ekonomi dan Bisnis Islam, 2024)
The Internal Control System (ICS) is a process designed and implemented by management, the board of commissioners, and all employees to provide reasonable assurance regarding the achievement of organizational objectives. Based on the COSO framework—which includes the control environment, risk assessment, control activities, information and communication, and monitoring—ICS plays a crucial role in safeguarding company assets, ensuring the reliability of financial reporting, improving operational efficiency, and promoting compliance with applicable regulations. This paper discusses the definition, objectives, elements, and structure of internal control, as well as the interrelationship between Internal Control and Accounting Information Systems (AIS). Effective internal control enables organizations to reduce recording errors, detect and prevent fraud, optimize the use of resources, and produce accurate, relevant, and timely financial information. The findings indicate that ICS functions not only as a monitoring mechanism but also as a strategic instrument that supports managerial decision-making and strengthens stakeholder trust. Therefore, an effective implementation of ICS is fundamental to achieving good governance and long-term organizational sustainability. Keywords: Internal Control System, COSO, Internal Control, Accounting Information System, Operational Efficiency, Financial Reporting Reliability.